New frontiers in engineering education: a systematic review on innovation and technologies in the post-COVID-19 context - Lizarzaburu Aguinaga, Danny Alonso; Pichis García, Roger Aban Hader; Pereyra Gonzales, Tony Venancio; Olivos Jímenez, Milagros Antonieta; Talaver Cubas, Marco Antonio; Silva León, Pedro Manuel; Arbulú Castillo, Julie Catherine (LACCEI, 2025)
This study addresses the radical transformation in engineering education, driven by the digital revolution and accelerated during the post-COVID-19 era. The adoption of emerging technologies such as artificial intelligence and virtual reality has redefined traditional teaching-learning paradigms in engineering faculties, although with disparities in implementation, especially in emerging regions. A systematic review of technological and pedagogical innovations implemented in engineering programs between 2018 and 2024 is presented, highlighting the integration of hybrid and virtual teaching modalities. This study identifies best practices and evaluates the effectiveness of technological interventions in resource-limited contexts, with a particular focus on Latin America. The findings align with the Sustainable Development Goals, emphasizing the importance of quality education and innovation.